2011
DOI: 10.1007/s11845-010-0670-4
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the European Working Time Directive on surgical training: the basic surgical trainee’s perspective

Abstract: Surgical training faces a challenge with the implementation of EWTD Rotas. Major changes need to be made to the surgical training structure to train surgeons to the highest standard and to retain Irish-trained surgeons in the Irish healthcare system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 5 publications
1
8
0
Order By: Relevance
“…10 Studies of the surgical specialties typically report surgeons to have a negative view of the EWTD. [11][12][13][14][15] Our findings confirm this. Previous studies of the views of surgical trainees have found concerns about reduced contact time with trainers, 14 reduced clinical exposure and operative experience 12 16 and adverse impact on patient care.…”
Section: The Impact Of the Ewtd On Junior Doctorssupporting
confidence: 85%
“…10 Studies of the surgical specialties typically report surgeons to have a negative view of the EWTD. [11][12][13][14][15] Our findings confirm this. Previous studies of the views of surgical trainees have found concerns about reduced contact time with trainers, 14 reduced clinical exposure and operative experience 12 16 and adverse impact on patient care.…”
Section: The Impact Of the Ewtd On Junior Doctorssupporting
confidence: 85%
“…This is in contrast to the demand stipulated by a recent publication on Improving Outcomes: A Strategy for Cancer by the Department of Health in the United Kingdom, which reinforced the aim of promoting the latest surgical techniques, including the training of the existing workforce and extending the benefits of surgical intervention to the older population (DOH, 2011). The issue of training surgeons to deliver high-quality care using minimally invasive surgery within the constraints of the European Working Time Directive (EWTD, 2009) is the main focus of discussions and workforce planning in the United Kingdom (Canter, 2011;Kelly et al, 2011;Simpson et al, 2011). Patient safety regulations and strict clinical governance would preclude performance of these complex techniques on live patients by novice surgeons.…”
Section: Introductionmentioning
confidence: 99%
“…Because laparoscopy requires other skills than open surgery, simulator-based skills training is currently widely accepted (2,3). However, we are still seeking optimal methods for assessing laparoscopic skills performance (4)(5)(6). In response to urgent calls from the government and the public for well-defined proficiency standards to safeguard the quality of care, the profession itself should accept its primary responsibility for patient safety and take the lead in setting proficiency standards based on professionals' knowledge and experience (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%